Effect of Functional Groups in Coal on the Depth of Adsorption Potential Well. (6th August 2021) - Wang, Chen; Feng, Zengchao; Wang, Xing
Abstract : Due to the complexity of the internal structure of natural coal and its characteristic of multicomponent, the depth of its methane adsorption potential well is nonuniform, which makes it difficult to accurately evaluate the adsorption capacity of coal. Besides, in order to find out the factors affecting the depth distribution of potential wells in natural coal, this paper calculated the depth and number of potential wells during methane adsorption in coal according to the Langmuir adsorption kinetics process. Coal samples with different metamorphic degrees were tested and analyzed by infrared spectroscopy diffraction technology. The relationship between the structural parameters of functional groups in coal samples with different metamorphic degrees and the distribution of different depths of adsorption potential wells in coal samples was studied. Some main conclusions are as follows: The number of adsorption potential wells at different depths in natural coal with different metamorphic degrees has multipeak distribution characteristics. With the increase of the metamorphic degree of coal sample, the structures such as aliphatic branched chain structure and oxygen-containing functional groups in coal structure break, fall off, and deoxygenate. The relative content of aliphatic hydrocarbons is significantly reduced and condensed into aromatic hydrocarbons and aromatic ring structures. The different types and quantities of functional groups on the surface of coal samples lead to different forces between coal molecules and methane gas molecules, thus affecting the distribution of different depths of adsorption potential wells in coal samples.